2010
DOI: 10.1051/0004-6361/201015426
|View full text |Cite
|
Sign up to set email alerts
|

Importance of level mixing on accurate [Fe II] transition rates

Abstract: Context. In a very recent measurement Gurell et al. (2009, A&A, 508, 525) commented that while the theoretical lifetime of a 4 G 5.5 is approximately one tenth of the lifetime of b 2 H 5.5 the corresponding measurement shows this to be close to one fifth. This large discrepancy is attributed to the effect of inadequate level mixing in the theoretical calculations. Aims. The aim of this work is to make a detailed analysis of these level mixing effects on transitions from various lower levels to the a 4 G 5.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This comparison also brings out observed lines with questionable identifications (e.g., λλ3968.27, 4889.71) and unreliable line-intensity ratios-e.g., I(λ7637.52)/I(λ9051.95), I(λ7686.93)/ I(λ8891.93), and I(λ7733.13)/I(λ9033.49)-due to A-values with magnitude log A −3. Theoretical A-value ratios agree to within 20-25% and, with respect to the observed line-intensity ratios, to within the error bars except for some outliers subject to strong level mixing, as pointed out in [40].…”
Section: Fe II Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This comparison also brings out observed lines with questionable identifications (e.g., λλ3968.27, 4889.71) and unreliable line-intensity ratios-e.g., I(λ7637.52)/I(λ9051.95), I(λ7686.93)/ I(λ8891.93), and I(λ7733.13)/I(λ9033.49)-due to A-values with magnitude log A −3. Theoretical A-value ratios agree to within 20-25% and, with respect to the observed line-intensity ratios, to within the error bars except for some outliers subject to strong level mixing, as pointed out in [40].…”
Section: Fe II Discussionsupporting
confidence: 80%
“…Excluding atom_SRKFB19_52, the A-value ratios in Tables 8 and 9 agree to ∼ 20−25% except for two cases in HH 202S, I(λ7637.52)/I(λ9051.95) and I(λ7686.93)/I(λ8891.93), and one in HH 204, I(λ7733.13)/I(λ9033.49), which are caused by lines with A-values of order 10 −3 subject to large numerical uncertainties. Most theoretical ratios are within the estimated observational error bars except for those involving A-values strongly affected by level mixing effects that are frequent in Fe II [40].…”
Section: A-value Ratio Benchmarksupporting
confidence: 66%
See 1 more Smart Citation
“…In calculations of M1 transitions within a multiplet, particularly in the lower-lying ones, most calculations agree, as shown in Deb & Hibbert (2010a). This is expected because the states involved are spectroscopically almost pure and the dipole matrix elements do not involve the radial functions.…”
Section: Resultsmentioning
confidence: 56%
“…For example, in their studies of E1 Fe II transitions, Corrégé and Hibbert (2005) [29], as well as Deb and Hibbert (2014) [30] found it better to choose a 3d function optimised on the energy of the ground 3d 6 4s 6 D state, whereas Deb and Hibbert (2010a,b,2011) [31][32][33], in studying forbidden transitions involving 3d 7 levels, found that much better results could be obtained by optimising the 3d function on the 3d 7 4 F state. This is possible when a calculation is limited to certain types of transition, or even to a very small number of transitions.…”
Section: Correlation In Open 3d Subshellsmentioning
confidence: 99%